Mathematical relations of models of single-phase flows in the channels of reactors and steam generators of NPP's for calculation of heat transfer processes and hydrodynamic characteristics - Yefimov, O.V.; Pylypenko, M.M.; Kavertsev, V.L.; Harkusha, T.A.; Tiutiunyk, L.J.; Motovilnik, A.V. (Вопросы атомной науки и техники, 2022)
The article presents the mathematical relationships of models of single-phase flows in channels of a other design for calculating the parameters of heat transfer processes and hydrodynamic (gas-dynamic) characteristics of flows. A comparative analysis of these ratios and their differences are indicated depending on the design of the channels. To calculate the processes of heat exchange in steam generators of nuclear power plants during the movement of single-phase flows of the coolant and working substance, the criterion equations of the similarity theory are used, which describe the generalized relationships between the quantities characterizing the processes that are similar to each other. These are the criteria for Re; Nu; Pr; Pe, et al. The article provides generalized relationships between similarity criteria for single-phase flows of different types of coolants (water, gas, liquid metals) and working substances that are used in the design and construction of reactors and steam generators. Представлені математичні співвідношення моделей однофазних потоків у каналах різного конструктивного виконання для розрахунку параметрів процесів теплообміну і гідродинамічних (газодинамічних) характеристик потоків. Проведено порівняльний аналіз цих співвідношень і вказані їх відмінності в залежності від конструктивного виконання каналів. Для розрахунку процесів теплообміну в парогенераторах АЕС при русі однофазних потоків теплоносія і робочої речовини застосовують критеріальні рівняння теорії подібності, які описують узагальнені залежності між величинами, що характеризують подібні між собою процеси. Це критерії Re; Nu; Pr; Pe та ін. Наведені узагальнені співвідношення між критеріями подібності для однофазних потоків теплоносіїв різних видів (водяних, газових, рідких металів) і робочих речовин, які використовуються в практиці проектування і конструювання реакторів і парогенераторів. Представлены математические соотношения моделей однофазных потоков в каналах разного конструктивного исполнения для расчета параметров процессов теплообмена и гидродинамических (газодинамических) характеристик потоков. Проведен сравнительный анализ этих соотношений и указаны их отличия в зависимости от конструктивного исполнения каналов. Для расчета процессов теплообмена в парогенераторах АЭС при движении однофазных потоков теплоносителя и рабочего вещества применяют критериальные уравнения теории подобия, описывающие обобщенные зависимости между величинами, характеризующими сходныe между собой процессы. Это критерии Re; Nu; Pr; Pe и др. Приведены обобщенные соотношения между критериями подобия для однофазных потоков теплоносителей различных видов (водяных, газовых, жидких металлов) и рабочих веществ, которые используются в практике проектирования и конструирования реакторов и парогенераторов.